Clinical Characteristics of Recurrent Nasopharyngeal Carcinoma in High-Incidence Area. (1st February 2012) - Li, Jia-Xin; Lu, Tai-Xiang; Huang, Ying; Han, Fei
Abstract : Background . To describe the clinical characteristics of the patients who suffered from relapse after conventional irradiation for nasopharyngeal carcinoma (NPC). Methods . Three hundred and fifty-one consecutive patients with first-time recurrent NPC between January 1999 and July 2005 were included. The patients' clinical data were reviewed, including recurrent interval time, symptoms, signs, imaging characteristics, pathologic features, and restaging. Results . The median interval of relapse was 26.0 months. The most common symptoms in symptomatic patients were nasal bloody discharge (37.9%) and headache (31.1%). Local recurrence alone accounted for 73.5%. Most patients were restaged as stage III (23.1%) and stage IV (51.1%). Subgroup analysis suggested a significantly higher proportion of the long-latent relapses originated from early primary. A series of postreirradiation complications were more frequent in patients with longer latency at reception. Conclusions . Most recurrent nasopharyngeal carcinoma is advanced disease. Patients with different recurrent interval time show different nature behavior.